2014
DOI: 10.1111/1750-3841.12640
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging Process on the Bioactive Components and Antioxidant Activity of Ginseng (Panax ginseng L.)

Abstract: The effects of aging process on the ginsenosides and antioxidant activity of ginseng was investigated. Fresh ginseng roots were aged in oven at 70 or 80 °C for 7, 14, 21, or 28 d. Their ginsenosides, phenolics, and antioxidant activity were analyzed. Ginseng aged at 80 °C for 14 d exhibited the highest amounts of total saponins and phenolics. It also showed markedly higher free radical scavenging activity, reducing power, and ferrous ion chelating ability than the other aged ginsengs. The ginsenosides Rb1 , Rb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Fresh ginseng roots (4 and 5 years old) were obtained from the Punggi Ginseng Cooperative Association (Yeongju, Korea). They were washed, placed in a plastic food container with a lid (15×20×10 cm) to keep them from drying out, and aged in an oven (SW 90D, Sang Woo Scientific Co., Bucheon, Korea) at 80°C with 70% relative humidity for 14 d. The aging temperature and time were selected based on the results of our previous study on the optimum aging processing conditions ( 11 ). The white and red ginseng samples (4 years old) were purchased from a local market in Daegu, Korea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh ginseng roots (4 and 5 years old) were obtained from the Punggi Ginseng Cooperative Association (Yeongju, Korea). They were washed, placed in a plastic food container with a lid (15×20×10 cm) to keep them from drying out, and aged in an oven (SW 90D, Sang Woo Scientific Co., Bucheon, Korea) at 80°C with 70% relative humidity for 14 d. The aging temperature and time were selected based on the results of our previous study on the optimum aging processing conditions ( 11 ). The white and red ginseng samples (4 years old) were purchased from a local market in Daegu, Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The red ginseng has been shown to have greater biological activity than the white ginseng due to its higher ginsenoside and phenolic contents ( 9 , 10 ). In our previous study, we found that aging could increase the amount of bioactive compounds and enhance the antioxidant activity of ginseng ( 11 ). The aging process involves heat treatment of ginseng roots in an oven for a specific period of time.…”
Section: Introductionmentioning
confidence: 99%
“…The main part of ginseng that has therapeutic effects is the root. Ginseng root has clinical and pharmacological effects such as anti-aging activity, anticancer activity, protection against circulatory shock effects; it also promotes immune function in human beings (Wang et al, 2005 ; Li et al, 2012 ; Kim and Cho, 2013 ; Bae et al, 2014 ). However, wild-type ginseng (W. Ginseng) is very scarce and unsustainable.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, a common mixture of active ingredients was demonstrated to be ginsensosides [ 3 , 4 , 5 ]. The benefits of ginseng are attributed to bioactive compounds, such as ginsenosides, volatile oils, polyphenols, flavonoids, polysaccharides, and vitamins [ 6 , 7 , 8 , 9 , 10 ]. In previous reports on physiological functions, ginseng exhibited anti-cancer [ 11 ], immunomodulatory [ 12 ], and antidiabetic [ 13 ] effects, and cardiovascular improvement [ 14 ] in delivering ginseng ginsenosides.…”
Section: Introductionmentioning
confidence: 99%